2007
DOI: 10.1074/jbc.m701419200
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Treatment of RAW264.7 Macrophages with Adiponectin Increases Tumor Necrosis Factor-α (TNF-α) Expression via ERK1/2 Activation and Egr-1 Expression

Abstract: Adiponectin is an adipokine with potent anti-inflammatory properties. However, the mechanisms by which adiponectin suppresses macrophage function are not well understood. Treatment of RAW264.7 macrophages with adiponectin for 18 h decreased lipopolysaccharide (LPS)-stimulated tumor necrosis factor-␣ (TNF-␣) production. Here we demonstrate that globular adiponectin (gAcrp) initially increased TNF-␣ expression in RAW264.7 macrophages; this TNF-␣ then contributed to increased expression of interleukin-10, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(162 citation statements)
references
References 44 publications
(66 reference statements)
9
145
2
2
Order By: Relevance
“…Truncations of the promoter to Ϫ161, deleting two B sites as well as the Egr-1 site, decreased TNF-␣ promoter/Luc activity by 70% over the 4-h treatment with gAcrp. This is consistent with previous data demonstrating a key role for Egr-1 and NFB in mediating increased TNF-␣ expression after 1-4-h exposure to gAcrp (12). However, after 24 h, TNF-␣ promoter/Luc activity was not affected by removal of these promoter elements (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Truncations of the promoter to Ϫ161, deleting two B sites as well as the Egr-1 site, decreased TNF-␣ promoter/Luc activity by 70% over the 4-h treatment with gAcrp. This is consistent with previous data demonstrating a key role for Egr-1 and NFB in mediating increased TNF-␣ expression after 1-4-h exposure to gAcrp (12). However, after 24 h, TNF-␣ promoter/Luc activity was not affected by removal of these promoter elements (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Phosphorylation of ERK1/2 and p38 MAPK and the quantity of IB were measured by Western blot analysis as described previously (12). Immunoreactive TTP was also measured by Western blot and normalized to Hsc70 as a loading control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 also suppresses cyclooxgenase-2 expression by downregulation of p38 MAPK and ERK2 (31). Moreover, several reports have shown that IL-10 inhibits ERK1/2 activity and that this is important, for example, for the downregulation of polymorphonuclear neutrophil functions and CD40-mediated induction of IL-1␤ and TNF-␣ synthesis by monocytes (6,33,39).…”
Section: Discussionmentioning
confidence: 99%
“…For example, long-term ethanol treatment increases LPS-induced TNF mRNA expression and TNF protein release by macrophages in an ERK-dependent manner (Kishore et al, 2002;Pritchard and Nagy, 2005). In addition, both pro-and anti-inflammatory effects of adiponectin on LPS-induced TNF release in RAW cells are mediated through ERK-dependent signaling (Park et al, 2007;Huang et al, 2008). ERK signaling plays a significant role in experimental models of inflammatory liver injury from alcohol or bile acid exposure (Mandrekar and Szabo, 2009;Allen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%